Design and synthesis of antifolates as potential antimalarial agents - Butsi, Kamogelo (My University, 2024)
Malaria still remains a life threatening disease in many parts of the world. According to the World Health Organisation (WHO) approximately 241 million cases of malaria were reported worldwide in 2020, with Africa being the most affected continent. Prevalence of the disease is attributed to the significant increase in resistance towards currently used chemotherapeutic agents. Therefore, the search for new antimalarial candidates is imperative. In this report, we give progress on the synthesis of novel 2,4- diaminopyrimidine derivatives and their respective activity against Plasmodium falciparum. We have successfully developed a synthetic route towards flexible 2,4- diaminopyrimidine derivatives, which entails the synthesis of these target compounds in five steps starting from commercially available esters. The Sonogashira reaction was the key step employed to functionalise the iodinated pyrimidine ring at the 5- position with a suitable acetylene to form an alkyne intermediate. In this way, a four atom linker was introduced between the heterocyclic ring system and the terminal phenoxy ring. Reduction of the triple bond in the alkyne intermediate by a hydrogenation reaction afforded a library of the desired flexible 2,4-diaminopyrimidine analogues. Of the synthesised compounds, 15 were sent for activity assessment against both wild type and mutant PfDHFR enzymes. They inhibited both PfDHFR enzymes at low nanomolar concentrations. Additionally, these compounds were also tested against the human DHFR to evaluate their selectivity. All tested compounds were selective for PfDHFR over human DHFR. Further assessment on the antiplasmodial activity of these compounds were conducted in vitro in a whole cell P. falciparum assay against the drug sensitive TM4/8.2 strain and the multidrug resistant strain V1S. The tested compounds displayed moderate antiplasmodial activity in the micromolar range with IC50 values of 0.28 – 23.4 µM and 17.`6 – 64.0 µM against the drug sensitive strain and multidrug resistant strain, respectively. Unfortunately, they were mild to highly cytotoxic towards VERO cells. Further interrogation of the selectivity index (SI) indicated that the tested compounds did not display any selectivity for the plasmodial parasite over VERO cells. Abstract iii Therefore, inhibition of the Plasmodium strains is not only due to compounds interacting with the parasite but also cytotoxicity of the compounds on the viability of erythrocyte.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023
Keywords: Malaria; Diseases